2007
DOI: 10.1002/jso.20766
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of vascular endothelial growth factors and their receptors in a series of angiosarcomas

Abstract: Background Angiosarcomas are malignant mesenchymal neoplasms, including sarcomas of presumptive vascular endothelial origin and sarcomas of probable lymphatic origin. It is, however, often difficult to determine whether they are from blood vascular or lymphatic endothelium. The majority of angiosarcomas are thought to originate from vascular endothelia and spread via bloodstream to lung, but lymphatic metastases can occur. Methods We investigated immunohistochemical expression of vascular endothelial growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 44 publications
3
96
0
3
Order By: Relevance
“…In infantile hemangioma, hemangioma-derived endothelial cells (hemeEC) have constitutively active VEGF receptor-2 signaling with high phosphorylation levels of ERK1/2 and Akt (3). Human angiosarcoma expresses VEGF-A and the VEGF receptors (4). We have shown increased phosphorylation of Akt and 4E-BP1 in angiosarcoma (5).…”
Section: Introductionmentioning
confidence: 85%
“…In infantile hemangioma, hemangioma-derived endothelial cells (hemeEC) have constitutively active VEGF receptor-2 signaling with high phosphorylation levels of ERK1/2 and Akt (3). Human angiosarcoma expresses VEGF-A and the VEGF receptors (4). We have shown increased phosphorylation of Akt and 4E-BP1 in angiosarcoma (5).…”
Section: Introductionmentioning
confidence: 85%
“…Immunohistochemical data from Itakura et al [16] demonstrated positive VEGFR-3 expression in 27 of 34 (79%) angiosarcomas; however none of these had breast origin. Gennaro et al [12], searching for VEGF re-expression, determined its expression levels in 20 breast specimens and found a significant association with low- and intermediate-grade tumors, suggesting the role of VEGF in the early carcinogenesis of angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…[108][109][110] Various reports have demonstrated overexpression of VEGFR-2 and VEGFR-3 and their corresponding ligands, VEGF-A, VEGF-C, in pulmonary and cutaneous angiosarcomas, denoting the paracrine and/or autocrine role in their development and proliferation. 90,124,125 Alveolar soft part sarcoma (ASPS) is known to be chemotherapy resistant and therefore development of novel agents is essential. Stacchioti et al 126 reported a series of 10 patients.…”
Section: Vascular Endothelial Growth Factors Fibroblast Growth Factomentioning
confidence: 99%